1990
DOI: 10.2527/1990.6851208x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and covariation in beef cow and bull fertility.

Abstract: Single-sire natural mating data from a beef cattle herd in tropical Australia were used to estimate heritabilities of cow fertility (hc2), heritabilities of bull fertility (hb2) and genetic correlations between cow and bull fertility (rg) within each of six genotypes. Estimates of hc2 and hb2 were low, averaging .11 and .08, respectively. The pooled estimate of rg was 0.16, indicating that cow and bull fertility are favorably genetically correlated and therefore that cow fertility could be genetically improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0
4

Year Published

1990
1990
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 0 publications
4
9
0
4
Order By: Relevance
“…Paralelamente, o perímetro escrotal tem sido preconizado como característica indicadora da puberdade em machos e nas fêmeas que apresentam algum parentesco com eles. Existe suporte na literatura para se concluir que os fatores hormonais que promovem o desenvolvimento testicular inicial nos machos são os mesmos que promovem o desenvolvimento ovariano inicial nas fêmeas, e a seleção para a puberdade precoce em um sexo resultará em associada redução da idade a puberdade do outro sexo (MACKINNON et al, 1990).…”
Section: Análises Envolvendo Mais De Uma Variávelunclassified
“…Paralelamente, o perímetro escrotal tem sido preconizado como característica indicadora da puberdade em machos e nas fêmeas que apresentam algum parentesco com eles. Existe suporte na literatura para se concluir que os fatores hormonais que promovem o desenvolvimento testicular inicial nos machos são os mesmos que promovem o desenvolvimento ovariano inicial nas fêmeas, e a seleção para a puberdade precoce em um sexo resultará em associada redução da idade a puberdade do outro sexo (MACKINNON et al, 1990).…”
Section: Análises Envolvendo Mais De Uma Variávelunclassified
“…Meyer et al (1990) obtained heritabilities of 0.08, 0.02 and 0.08 for calving success in Herefords, Angus and Zebu crosses respectively, while Mackinnon et al (1990) reported an average heritability estimate for cow fertility of 0.11. The heritability of 0.08 for longevity was also low and corresponds with other estimates (Parker et al, 1959;Miller et al 1967;Hudson & Van Vleck, 1981).…”
Section: Figure 2 Calving Percentage Of Dams Of Different Dam-birth Amentioning
confidence: 99%
“…However, there is significant genetic variation between cows in the interval from calving to first breeding, which is positively correlated with number of services per conception (NSC) (Milagres et al. 1979; Mackinnon et al. 1989; Meyer et al.…”
Section: Introductionmentioning
confidence: 99%